BETWEEN LIKES AND PURCHASES: EVIDENCE ABOUT THE ROLE OF DIGITAL INFLUENCERS IN GENERATION Z CONSUMPTION IN JUIZ DE FORA/MG - de Matos, Anna Júlia Delgado; de Oliveira, Victor Miranda; de Oliveira Mendes, Tatiana Dornelas (Seven Editora, 2025)
This study investigated the role of digital influencers in the consumption decisions of Generation Z residing in Juiz de Fora, Minas Gerais, using a mixed quantitative and qualitative descriptive approach. The objective was to analyze how digital influencers impact the purchasing decisions of this audience, identifying determining factors and consumption patterns. To this end, biblioFigureic and field research was conducted, with a structured questionnaire applied to young people between 18 and 30 years of age who are frequent users of social networks. The data were statistically analyzed and interpreted in light of correlations between sociodemoFigureic profile, digital habits, and purchasing behavior. The results indicate that most respondents have made purchases motivated by influencers, with credibility, practical demonstrations, and authenticity being the main influencing factors. It was also observed that, although the influence is significant, the frequency of purchases is predominantly sporadic, with the greatest impact in the fashion, beauty, and food segments. It is concluded that influencer marketing plays a relevant role among young adults, but its effectiveness depends on the authenticity and perceived relevance of the content to the audience. DOI: https://doi.org/10.56238/sevened2025.029-090